A mobile device tool to assist the ECG interpretation based on a realistic 3D virtual heart simulation. (June 2018) - Coelho, Regina Célia; Rangel Lourenço, Nayara Consuelo Gomes; de Godoy, Carlos Marcelo Gurjão
Computational tools can be developed to help the interpretation of the ECG and the beating heart. In some cases, such tools are implemented in mobile devices and applied to "mobile learning" (m-learning) activities. In the present work, we show a mobile device tool that emulates the beating heart according to ECG data. The tool has been implemented using skeletal subspace deformation to control the movement of a 3D heart model in real time. It is possible to manipulate the heart model and visualize its inner anatomy. The results of the simulation show that the tool allows online adjustments on the virtual heart according to actual ECG data set by the user or by ECG data files (normal rhythm or arrhythmias). The comparison between clinical data and the results of the simulation validated the cardiac beating simulation. The user experience was evaluated by students of biomedical engineering using a Likert scale. The students evaluated their experience with the tool positively. The results, as a whole, show that the tool may represent a newly accessible resource to help support m-learning in the context of interpreting ECG data. Also, the tool seems to be applicable in a teaching/learning environment where undergraduates are studying either the ECG or the cardiac anatomy or function.